Veblen 2.0: Neoliberal Games of Social Capital and the Attention Economy as Conspicuous Consumption - Kane Xavier Faucher (tripleC: Communication, Capitalism & Critique)
The purpose of this article will be in reading acts of prosumer behaviour in social networking environments through a Veblenian lens, supported in part by the post-Marxist insights of Guy Debord, especially with respect to the issue of celebrity emulation, conspicuous leisure as constructed by the labour of profile management and promiscuous online interactivity, and acts of status enhancement or aggrandizement. Such a discussion must be set in the current context of the normative frame of neoliberal ideology which champions the values of the entrepreneurial self, devolved competitiveness as a form of - in this case social rather than strictly economic - neo-Darwinism, and the touted virtues of speed and connectivity. Ultimately, it is our hope to link these conspicuous online practices to the ideological framework to demonstrate how prosumption plays an integral role in the quantification of the social economy as expressed as “social capital.” In order to achieve these objectives, strict and operational definitions of prosumption, conspicuity in the Veblenian literature, and neoliberalism will be required. The line between social and economic capital is not a definitive one, and that the behaviours and motives associated with increasing social capital may be weighted more to the individual and influenced by neoliberal values that recode the social as derivative of the economic.